Party Autonomy - Cooke, Robin (Victoria University of Wellington Law Review, 1999)
This is an augmented version of a paper delivered at the International Centre for Alternative Dispute Resolution, New Delhi, in December 1998. Party autonomy describes the principle whereby the parties to a dispute have full autonomy when making their arbitration agreement. The author discusses the Arbitration and Conciliation Act 1996 of the Parliament of India, focusing on the principle of party autonomy. He describes his formative experiences to arbitration in cases like Wellington City v National Bank of New Zealand Properties Ltd, the Arbitration and Conciliation Act itself, Indian case law before the Arbitration and Conciliation Act, and a brief look at New Zealand's Arbitration Act 1996.